Visualize Complex Processes with Microsoft Visio : A guide to visually creating, communicating, and collaborating business processes efficiently /: A guide to visually creating, communicating, and collaborating business processes efficiently. (2023) - Parker, David J; Lelić, Šenaj
No abstract available